Transcatheter aortic valve implantation with a Sapien 3 Commander 20 mm valves in patients with degenerated 19 mm bioprosthetic aortic valve. Issue 7 (3rd October 2016) - Loyalka, Pranav; Nascimbene, Angelo; Schechter, Michael; Petrovic, Marija; Sundara Raman, Ajay; Gregoric, Igor D.; Kar, Biswajit
Abstract : Introduction: Transcatheter aortic valve implantation (TAVI) in patients with degenerated bioprosthetic aortic valve has been successfully performed as an alternative to surgery. We describe our initial experience of valve‐in‐valve TAVI in five patients, using new generation Edwards Sapien 3 transcatheter heart valves implanted into degenerated 19 mm bioprosthetic valves. 20‐mm Edwards S3 valves were offered for compassionate use. All patients had significant aortic valve stenosis. Methods and Results: The main vascular access was achieved and pre‐closed with two Proglide closure devices in one patient and Prostar closure devices in four patients. For each TAVI procedure an Edwards 14 French sheath was inserted without complication and sutured in place. The Sapien 3 Commander delivery system was inserted and the valve was aligned in the descending aorta. The 20‐mm Sapien 3 valve was deployed with slow continuous inflation during rapid right ventricular pacing. The cranial edge of the Edwards S3 valve was aligned with the cranial radiopaque markers of bioprosthesis to minimize paravalvular leak. Post‐deployment angiography, transesophageal echocardiography and aortogram confirmed absence of mild aortic insufficiency and no increase in trans‐aortic gradient when compared to a naïve 19 mm bioprosthetic valve. Conclusion: Valve‐in‐valve TAVI with the Edwards S3 transcatheter heart valve for degenerative bioprosthetic aortic valves is technically feasible. The proper position of the stented valve minimizes the risk for post‐procedure paravalvular insufficiency and provides good transaortic pressure gradient. © 2016 Wiley Periodicals, Inc.